2014
DOI: 10.1161/strokeaha.114.004695
|View full text |Cite|
|
Sign up to set email alerts
|

Is More Better? Using Metadata to Explore Dose–Response Relationships in Stroke Rehabilitation

Abstract: Background and Purpose Neurophysiological models of rehabilitation and recovery suggest that a large volume of specific practice is required to induce the neuroplastic changes that underlie behavioral recovery. The primary objective of this meta-analysis was to explore the relationship between time scheduled for therapy and improvement in motor therapy for adults post-stroke by (1) comparing high-doses to low-doses and (2) using meta-regression to further quantify the dose-response relationship. Methods Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
415
5
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 507 publications
(450 citation statements)
references
References 59 publications
15
415
5
15
Order By: Relevance
“…Because it had not been previously established that rehabilitation drives enhancement of brain structure immediately surrounding a lesion site, the value and importance of intense rehabilitation of lost functions may not have been fully appreciated. Although studies generally support the concept that more frequent rehabilitation is associated with improved outcomes after stroke (30)(31)(32)(33)(34), few clinical trials have specifically tested whether highly repetitive, narrowly focused rehabilitation improves motor outcomes (29). Prospective, controlled, and adequately powered studies addressing this specific point have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Because it had not been previously established that rehabilitation drives enhancement of brain structure immediately surrounding a lesion site, the value and importance of intense rehabilitation of lost functions may not have been fully appreciated. Although studies generally support the concept that more frequent rehabilitation is associated with improved outcomes after stroke (30)(31)(32)(33)(34), few clinical trials have specifically tested whether highly repetitive, narrowly focused rehabilitation improves motor outcomes (29). Prospective, controlled, and adequately powered studies addressing this specific point have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Task-specific motor training involves high intensity practice. Intensity is not consistently defined in the rehabilitation literature, referring to number of repetitions (Taub et al, 2013), amount of work or effort (Kwakkel, 2006) or duration of practice (Lohse, Lang, & Boyd, 2014). Amount of work or effort is difficult to measure for tasks such as handwriting that do not involve a defined energy output.…”
Section: High Intensity Practicementioning
confidence: 99%
“…Intensity is important in stroke rehabilitation, with greater doses of therapy yielding greater improvements in function. A meta-analysis was conducted on the effects of increased therapy time on motor recovery post-stroke (Lohse et al, 2014). This meta-analysis of 37 RCTs found that adults with stroke who received more hours of therapy time (mean 33 hours extra) had greater improvements in motor function than those who received less hours of therapy (g = 0.35; 95% CI: 0.26 to 0.45).…”
Section: High Intensity Practicementioning
confidence: 99%
“…However, the authors did not comment on the lower than intended dosage or explicitly consider how this may have impacted their findings. Given our emerging understanding of the relation between dose of therapy and functional gains, 8,9 this may be a key limitation of the present work. The venue for therapy was at home for Home CIMT but the authors do not state whether the majority of sessions took place in a clinic setting for the standard care group.…”
Section: Boyd and Walker Critique Of Home Cimt Trialmentioning
confidence: 98%